Konflik Batin dan Mekanisme Pertahanan Diri Tokoh Ikrimah bin Abu Jahal dalam Drama Zaujatān Ṣāliḥatān Karya Ali Ahmad Bakatsir melalui Psikoanalisis Freud - Ramadhani, Yus; Syah, Ahfa Rahman; Novita, Lidya; Amelia, Rosita (Study Program of Arabic Language Teaching, 2026)
This study analyzes the internal conflicts and defense mechanisms of Ikrimah ibn Abu Jahal through the lens of Sigmund Freud’s psychoanalytic framework. Employing a qualitative descriptive-analytical approach that utilizes content analysis and the